PENGGUNAAN ANALISIS SWOT DALAM PENANGANAN MITIGASI KORUPSI STUDI KASUS DESA ADI PURWA - Witri Nurhikmah; Bayu Arinanto; Sabrina Amanda Fitri; Ridho Akbar; Ahmad Baidawi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Corruption in the management of village funds is a major challenge that hinders development at the local level. This research discusses corruption mitigation strategies in Adi Purwa Village through a SWOT analysis and project management approach. The research results show that weak internal supervision, low capacity of village officials, and minimal community participation are the main causes of corruption. The SWOT analysis approach helps identify strengths, weaknesses, opportunities and threats in village fund governance, while project management provides a framework for designing effective mitigation measures. Strategies such as financial digitalization and community involvement in supervision have been proven to increase accountability and transparency. It is hoped that the implementation of this strategy can make Adi Purwa Village a model village that is free of corruption and contributes to sustainable development.